Stability analysis of stochastic Ricker population model - Natali Hritonenko; Alexandra Rodkina; Yuri Yatsenko (Discrete Dynamics in Nature and Society)
A stochastic generalization of the Ricker discrete population model is studied under the assumption that noise impacts the population reproduction rate. The obtained results demonstrate that the demographic-type stochastic noise increases the risk of the population extinction. In particular, the paper establishes conditions on the noise intensity under which the population will extinct even if the corresponding population with no noise survives.